Corporate-supported research in a reengineered technology organizations - Detz, Clifford M.
Clifford M. Detz tells how Chevron revamped its long-range research to complement the more immediate focus of the technology activities its business units fund.
A long-range research program complements the shorter-range technology activities that Chevron's business units fund.
As pressure to improve short-term financial performance has increased, longer-range research programs, particularly those at a corporate level, have fallen victim to cost-cutting initiatives. This development jeopardizes the technology base that sustains the corporation's businesses in both the short and long term. By designing a corporate long-range research program that is explicitly aligned with corporate business drivers, and the strategy of which is guided by management representatives from the major businesses, a credible and sustainable long-range research program can be developed. A key to success is an emphasis on transferring results of the longer-range program to specific business units as those results mature, and a metric to keep track of this transfer. The metric provides visible evidence of the relevance of the program to the business units of the corporation.
Keywords: Technology organizations